Framing Analysis of Environmental Issues in the New Indonesian Capital City (IKN) on Kompas.id - Kian Santang, Ahmad; Nur Aini, Prashasti; Ashshiddiqi, Fauzan; Atmaja, Ika Listiyadi Julia; Kusumaningrum, Rizki (Jurnal Mengkaji Indonesia, 2024)
Abstract: This paper aims to determine how the framing of environmental news in the Indonesian media, in this case, Kompas.id media as the object of research. News related to environmental issues on the topic of IKN development on Kompas.id media in the range of August 2022 - November 2022 were collected and analyzed using the framing analysis model by Robert Entman. From the analysis, it was found that Kompas gave significant attention to constructive news about the IKN project, especially in the context of physical and infrastructure development. In addition, it was also found that socio-cultural aspects were also a concern in Kompas news, with an emphasis on the Balik Tribe and Paser Tribe communities that inhabit the IKN development area. Purpose: This paper aims to determine how the framing of environmental news in the Indonesian media, in this case, Kompas.id media as the object of research Design/Methodology/Approach: This study is descriptive qualitative research, using Entman’s framing analysis model. Findings: This research presents that Kompas gave significant attention to constructive news about the IKN project, especially in the context of physical and infrastructure development. In addition, it was also found that socio-cultural aspects were also a concern in Kompas news, with an emphasis on the Balik Tribe and Paser Tribe communities that inhabit the IKN development area. Originality/value: This research's originality lies in its analysis of how Kompas.id frames environmental news regarding the new Indonesian capital city project (IKN), providing insights into media influence on public perception and decision-making on major development projects. Additionally, the study includes a focus on socio-cultural aspects, offering a unique perspective on the topic.